Improving Student’s Listening Skill through Bingo Game: A Classroom Action Research at Fifth Grade Students in Sidomulyo - Arif Pranata Perangin-angin; Bahagia Tarigan; Umar Mono (Talenta Publisher, 2022)
This research aims to find out and describe the improvement of students’ listening skill through bingo game. Classroom Action Research (CAR) designed by Kemmis and Mc Taggart which consisting of four phase in each cycle: planning, acting, observing, and reflecting was used as the research method. In obtaining the result, there were two types of data collection: the qualitative data (observation and interview) and the quantitative data (pre-test and post-test). In analyzing the data, descriptive analysis and statistic analysis were used to find out the result of bingo game implementation. The result showed that the use of bingo game improved the students’ score and their responses were good. For the students’ responses, it can be seen through the observation and interview taken. In addition, the improvement of the students’ achievement were proved after the tests in each cycle (pre-test, post-test I, and post-test II) taken: the students’ mean score in pre-test was 57.25 and the students’ mean score in post-test II was 75 which the improvement of the students’ mean score in pre-test and post-test II was 17.75. Then, the percentage of the students who met the KKM in pre-test was 35%, post-test I was 65% and post-test II was 85%. In summary, the result showed that the implementation of the Classroom Action Research met the target CAR (75%) which means that the Classroom Action Research was successful.